KAJIAN RUNWAY END SAFETY AREA DI BANDARA INTERNASIONAL ADISUTJIPTO YOGYAKARTA - Nurhedhi Desryanto (Langit Biru: Jurnal Ilmiah Aviasi, 2018)
Due to the increasing requirements of aviation safety standards demanded by the international aviation world and in line with the process of disseminating civil aviation safety regulations as well as Civil Aviation Safety Regulations (CASR) 139 on Aerodrome, it is mandatory for each airport to complete aviation safety facilities, Runway End Safety Area (RESA) at airports in Indonesia, given the technical classification of each airport as well as the area around the airport which is generally very limited. Adisutjipto International Airport is close to the Boko mountains, so when the weather is bad, visibility in the area becomes low, from this natural condition, space is required as a safety area with certain construction, in case of an emergency condition capable of being burdened by the body aircraft or firefighting and fire-fighting vehicles (PKP-PK). So RESA is considered important to be provided at Adisutjipto International Airport Yogyakarta, considering several accidents have occurred at the airport. In addition to improving safety operations, RESA manufacturing is also to meet the aviation safety standards demanded by the international aviation world. As far as it can be done, RESA should be prepared or built in such a way as to reduce the risk of damage to aircraft, increase airplane retarding power, and smooth the movement of PKP-PK vehicles.